A naval history of the Peloponnesian War : ships, men and money in the war at sea, 431-404 BC - DeSantis, Marc G. (Pen & Sword Maritime, 2017)
"Naval power played a vital role in the Peloponnesian War. The conflict pitted Athens against a powerful coalition including the preeminent land power of the day, Sparta. Only Athens' superior fleet, her 'wooden walls', by protecting her vital supply routes allowed her to survive. It also allowed the strategic freedom of movement to strike back where she chose, most famously at Sphacteria, where a Spartan force was cut off and forced to surrender. Athens' initial tactical superiority was demonstrated at the Battle of Chalcis, where her ships literally ran rings round the opposition but this gap closed as her enemies adapted. The great amphibious expedition to Sicily was a watershed, a strategic blunder compounded by tactical errors which brought defeat and irreplaceable losses. Although Athens continued to win victories at sea, at Arginusae for example, her naval strength had been severely weakened while the Spartans built up their fleets with Persian subsidies. It was another naval defeat, at Aegispotomi (405 BC) that finally sealed Athens' fate. Marc DeSantis narrates these stirring events while analysing the technical, tactical and strategic aspects of the war at sea."--